Implementation of Curriculum Merdeka in Early Childhood Education (PAUD): Literature Study on Opportunities and Obstacles - Garnika, Eneng; Rohiyatun, Baiq (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to examine in depth the opportunities and obstacles in implementing the Merdeka Curriculum at the Early Childhood Education (PAUD) level through a literature study approach. Merdeka Curriculum is presented as an effort to transform national education which is more flexible and learner-centered. In the context of PAUD, this curriculum emphasizes a play-based holistic approach and character strengthening through the Pancasila Student Profile Strengthening Project (P5). This study analyzes a range of relevant secondary sources, including scientific journals, policy documents and educational reference books, spanning the period 2019-2024. The results show that the main opportunities for implementing Merdeka Curriculum include learning flexibility, teachers’ freedom in developing teaching modules, and a fun contextual approach. However, a number of obstacles were also identified, such as uneven teacher readiness, limited infrastructure, overlapping curriculum understanding, and lack of parental involvement. This study recommends the need for continuous training, increased collaboration between teachers and parents, and strengthening learning communities in PAUD environments to support the optimal implementation of Merdeka Curriculum. Keywords: Merdeka Curriculum, PAUD, Implementation Barriers Â